Assessing the Impact of Restrictive Housing on Inmate Post-Release Criminal Behavior - Zgoba, Kristen (American journal of criminal justice, 2020)
The placement of inmates in restrictive housing (RH) units has become a staple of corrections policy in recent years. Despite its increased use, research on its continued effects is relatively rare when compared to the breadth of general correctional research. This study contributes to the literature by examining the effect placement in restrictive housing has on offender recidivism post prison release. Subjects include approximately 4000 inmates matched through Propensity Score Matching (PSM) techniques and followed 36 months post-release. The findings reveal that inmates placed in restrictive housing had elevated levels of recidivism and proportionally more new commitments for all crime types than those not placed in restrictive housing. Restrictive housing subjects also displayed shorter time to rearrest than non-RH individuals. The theoretical and policy implications of these findings are discussed.